(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In large companies, the integration of advanced accounting theories and practices-including strategic management accounting, comprehensive financial reporting, rigorous auditing, budgeting, and the adoption of digital technologies-serves as a cornerstone for enhancing financial performance, organizational governance, and long-term sustainability. The complexity and scale of large firms necessitate the adoption of sophisticated accounting frameworks, which not only facilitate compliance and transparency but also drive strategic decision-making, risk management, and competitive advantage. Empirical studies confirm that when large organizations invest in adaptive, technology-driven accounting systems and align them with international standards and contextual business variables, they achieve superior operational outcomes, reduced fraud, and greater stakeholder trust.